Different Neural Responses to Stranger and Personally Familiar Faces in Shy and Bold Adults. - Beaton, Elliot A.; Schulkin, Jay; Swinson, Richard P.; Schmidt, Louis A.; Antony, Martin M.; Hall, Geoffrey B. (Behavioral Neuroscience, 2008)
The shy-bold continuum is a fundamental behavioral trait conserved across human and nonhuman animals. Individual differences along the shy-bold continuum are presumed to arise from, and are maintained by, differences in the excitability of forebrain limbic areas involved in the evaluation of stimulus saliency. To test this hypothesis, the authors conducted an event-related functional MRI (fMRI) study in which brain scans were acquired on shy and bold adults during the presentation of neutral stranger and personally familiar faces. Shy adults exhibited greater bilateral amygdala activation during the presentation of stranger faces and greater left amygdala activation during personally familiar faces than their bold counterparts. Bold adults exhibited greater bilateral nucleus accumbens activation in response to stranger and personally familiar faces than shy adults. Findings suggest that there are distinct neural substrates underlying and maintaining individual differences along a shy-bold continuum in humans. Reprinted by permission of the publisher.